Spatial soundscape superposition, Part I: Subject motion and scene sensibility - Cohen, Michael; Martens, William L. (Acoustical Science and Technology, 2020)
Spatial soundscape superposition occurs whenever multiple sound signals impinge upon a human listener's ears from multiple sources, as in augmented reality displays that combine natural soundscapes with reproduced soundscapes. Part I of this two-part contribution on spatial soundscape superposition regards perceptual superposition of soundscapes, and therefore focusses upon human response to displayed auditory scenes, and the influence of subject (listener) motion on making sense of them in the context of information received from other sensory systems, especially the visual and vestibular systems. Consideration of listener motion and multimodal integration here is intended to lay the foundation for Part II of this contribution, which focusses upon physical stimuli, i.e., sounds and signals, and the systems used to mix, transmit, and display them. Through superposition of complex sound stimuli at the ears of a moving listener, these systems create complex auditory scenes, the nature of which cannot be predicted by simple combination of physical stimuli. As it is left to the human listener to interpret auditory scenes comprising those stimuli, this part focuses upon perceptual principles, such as grouping principles, that can aid in successfully predicting whether multiple auditory events are perceptually segregated or fused in the auditory scenes that are experienced. Furthermore, for moving listeners, four fundamental laws are identified here describing sensorimotor contingencies that enable prediction not only of what auditory images are formed, but also where in auditory space those images are likely to be perceived.